2022
DOI: 10.1037/tmb0000082
|View full text |Cite
|
Sign up to set email alerts
|

Do students learn better with immersive virtual reality videos than conventional videos? A comparison of media effects with middle school girls.

Abstract: This article presents two studies comparing the effects of educational immersive virtual reality (IVR) versus traditional videos on conceptual knowledge and self-efficacy. Learning was measured through multiple-choice questions assessing conceptual knowledge and open-ended questions assessing knowledge understanding, knowledge application, and knowledge creation, based on Bloom's taxonomy of learning objectives. In Experiment 1, 53 eighth-grade students from an all-girls school learned about humans' impact on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 76 publications
1
6
0
Order By: Relevance
“…Many are excited to incorporate this type of technology into classrooms, as it feels futuristic and effective in motivating students to learn (Bailenson, 2018; Blascovich & Bailenson, 2012). This technology can aid in learning by transporting a learner to an environment they would otherwise not be able to be in—like a different country or to the bottom of the ocean—or changing the scale of the world to allow for observations that would otherwise not be able to happen—like sizing the solar system down to allow for the observation of moon phases or sizing up a cell to allow for observation of cell division—or changing the speed at which processes occur—like slowing down space travel to understand special relativity or speeding up climate change (e.g., Barnidge et al, 2021; Madden et al, 2020; Makransky & Mayer, 2022; Parong & Mayer, 2018, 2021a, 2021b; Queiroz et al, 2022; Tarng et al, 2022). As a specific example, IVR can be used so students can learn about ocean acidification by watching carbon dioxide molecules come from car exhaust, how the molecules mix with ocean water, and the impact they have on sea life all while the participant is ‘in’ an underwater reef.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many are excited to incorporate this type of technology into classrooms, as it feels futuristic and effective in motivating students to learn (Bailenson, 2018; Blascovich & Bailenson, 2012). This technology can aid in learning by transporting a learner to an environment they would otherwise not be able to be in—like a different country or to the bottom of the ocean—or changing the scale of the world to allow for observations that would otherwise not be able to happen—like sizing the solar system down to allow for the observation of moon phases or sizing up a cell to allow for observation of cell division—or changing the speed at which processes occur—like slowing down space travel to understand special relativity or speeding up climate change (e.g., Barnidge et al, 2021; Madden et al, 2020; Makransky & Mayer, 2022; Parong & Mayer, 2018, 2021a, 2021b; Queiroz et al, 2022; Tarng et al, 2022). As a specific example, IVR can be used so students can learn about ocean acidification by watching carbon dioxide molecules come from car exhaust, how the molecules mix with ocean water, and the impact they have on sea life all while the participant is ‘in’ an underwater reef.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chamba-Eras and Aguilar ( 2017 ) state that AR is recommended to compensate various deficiencies that might occur in a smart classroom such as difficulties in doing complicated and dangerous experiments, carrying out actual experiments due to equipment costs, and unavailability of appropriate facilities. Furthermore, the study from Stanford University has shown that students who learn with AR technology demonstrate greater knowledge retention and improved problem-solving skills (Queiroz et al, 2022 ). The importance of Augmented Reality technology in education has led to its implementation in various topics as shown in Table 5 :…”
Section: Key Technologies Related To Smart Classesmentioning
confidence: 99%
“…Although much remains to be discovered about the potential role VR can play in broad climate change education and behaviors, recent media and design comparison studies have shown the benefits of using VR instead of computer monitors in some of the factors identified by van Valkengoed and Steg [14], such as knowledge [21][22][23][24], risk perception [25], involvement with nature [25], positive and negative affect [26], pro-environmental behavior [19,27,28], trust [29], and factors related to learning, such as self-efficacy toward science [22,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies using VR to teach OA have shown that users' movement in VR underlies the media effects on knowledge gains [21] and self-efficacy toward learning [22]. Research from multiple backgrounds has demonstrated that body movement is essential in learning [44][45][46][47][48][49][50], creating social and psychological attachments to the environment [51], and inducing attitude and behavior change [52].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation